Diagnostic modalities for nonalcoholic fatty liver disease, nonalcoholic steatohepatitis, and associated fibrosis. Issue 1 (5th July 2018) - Younossi, Zobair M.; Loomba, Rohit; Anstee, Quentin M.; Rinella, Mary E.; Bugianesi, Elisabetta; Marchesini, Giulio; Neuschwander‐Tetri, Brent A.; Serfaty, Lawrence; Negro, Francesco; Caldwell, Stephen H.; Ratziu, Vlad; Corey, Kathleen E.; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a spectrum comprised of isolated steatosis, nonalcoholic steatohepatitis (NASH), advanced fibrosis, and cirrhosis. The majority of NAFLD subjects do not have NASH and do not carry a significant risk for liver‐related adverse outcomes (cirrhosis and mortality). Globally, the prevalence of NAFLD is approximately 25%. In Asia, a gradient of high to low prevalence rates is noted from urban to rural areas. Given the prevalence of NAFLD, the clinical and economic burden of NAFLD and NASH can be substantial. With increasing recognition of NASH as an important liver disease, the diagnosis of NASH still requires a liver biopsy that is suboptimal. Although liver biopsy is the most accurate modality to diagnose and stage the severity of NASH, this method suffers from being invasive, costly, associated with potential complications, and plagued with interobserver variability of individual pathological features. A number of noninvasive modalities to diagnose NASH and stage liver fibrosis are being developed. These modalities include predictive models (NAFLD fibrosis score) and serum biomarkers such as enhanced liver fibrosis (ELF). Other tests are based on radiological techniques, such as transient elastography (TE) or magnetic resonance elastography (MRE), which are used to estimate liver stiffness as a potential surrogate of hepatic fibrosis. Although a dynamic field of research, most of these diagnostic modalities have area under the curve ranging between 0.76 and 0.90%, with MRE having the best predictive performance. In summary, developing safe and easily accessible noninvasive modalities to accurately diagnose and monitor NASH and associated fibrosis is of utmost importance in clinical practice and clinical research. These tests are not only important to risk stratify subjects at the greatest risk for progressive liver disease, but also to serve as appropriate surrogate endpoints for therapeutic clinical trials of NASH. (Hepatology 2018;68:349‐360).